Multiple positive solutions for singular higher-order semipositone fractional differential equations with p-Laplacian - Zhong, Qiuyan; Zhang, Xingqiu; Gu, Lufeng; Lei, Lei; Zhao, Zengqin (Nonlinear Analysis: Modelling and Control, 2020)
In this article, together with Leggett–Williams and Guo–Krasnosel’skii fixed point theorems, height functions on special bounded sets are constructed to obtain the existence of at least three positive solutions for some higher-order fractional differential equations with p-Laplacian. The nonlinearity permits singularities both on the time and the space variables, and it also may change its sign.
Keywords: fractional differential equations; height functions; singularity on space variable; semipositone; triple positive solutions